Psychosocial and organizational risk management, a bibliometric analysis. - Rivera-Porras, Diego (AiBi Journal of Research, Administration and Engineering, 2019)
The objective of this article is to carry out a bibliometric analysis of the conceptualization of psychosocial risk and its factors from the workplace. For the fulfillment of the investigative purpose, it was carried out through a documentary bibliographic design, through secondary data as a source of information, that is, analyzing data collected in previous investigations. Concluding that psychosocial risk factors can become a means of health or illness for workers.